Chloroplast Stromules Function during Innate Immunity - Caplan, Jeffrey L.; Kumar, Amutha Sampath; Park, Eunsook; Padmanabhan, Meenu S.; Hoban, Kyle; Modla, Shannon; Czymmek, Kirk; Dinesh-Kumar, Savithramma P. (Developmental cell, 2015)
Inter-organellar communication is vital for successful innate immune responses that confer defense against pathogens. However, little is known about how chloroplasts, which are a major production site of pro-defense molecules, communicate and coordinate with other organelles during defense. Here we show that chloroplasts send out dynamic tubular extensions called stromules during innate immunity or exogenous application of the pro-defense signals, hydrogen peroxide (H2O2) and salicylic acid. Interestingly, numerous stromules surround nuclei during defense response, and these connections correlate with an accumulation of chloroplast-localized NRIP1 defense protein and H2O2 in the nucleus. Furthermore, silencing and knockout of chloroplast unusual positioning 1 (CHUP1) that encodes a chloroplast outer envelope protein constitutively induces stromules in the absence of pathogen infection and enhances programmed cell death. These results support a model in which stromules aid in the amplification and/or transport of pro-defense signals into the nucleus and other subcellular compartments during immunity. [Display omitted] •Chloroplast stromules are induced during plant immune responses•Pro-PCD signals such as SA and H2O2 induce stromules•Stromules form dynamic connections with nucleus during immune responses•Constitutively induced stromules enhance PCD during plant immune responses Caplan et al. show that dynamic tubular projections from chloroplasts called stromules are induced during a plant immune response. Stromules form connections with the nucleus and may aid in the transport of pro-defense signals. Stromules enhance programmed cell death and may facilitate its progression during an immune response.